2021
DOI: 10.21037/atm-20-4332
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of vascular iatrogenic trauma and endovascular treatment

Abstract: Iatrogenic injury is unfortunately a leading cause of morbidity and mortality for patients worldwide. The etiology of iatrogenic injury is broad, and can be seen with both diagnostic and therapeutic interventions. While steps can be taken to reduce the occurrence of iatrogenic injury, it is often not completely avoidable. Once iatrogenic injury has occurred, prompt recognition and appropriate management can help reduce further harm. The objective of this narrative review it to help reader better understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…10 In our case, the prone position ensured that the abdominal structures became pressed against the vertebral bodies, rendering the retroperitoneal vessels fixed in close proximity to the anterior longitudinal ligament. 12 In addition, from the imaging point of view, the calcification of the patient’s aorta was very severe, making the vessel less elastic, and the anterior edge of the L2 vertebral body was ruptured. Most importantly, the end of the bone grafting funnel is sharp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In our case, the prone position ensured that the abdominal structures became pressed against the vertebral bodies, rendering the retroperitoneal vessels fixed in close proximity to the anterior longitudinal ligament. 12 In addition, from the imaging point of view, the calcification of the patient’s aorta was very severe, making the vessel less elastic, and the anterior edge of the L2 vertebral body was ruptured. Most importantly, the end of the bone grafting funnel is sharp.…”
Section: Discussionmentioning
confidence: 99%
“…10 Minimally invasive endovascular techniques have been used increasingly as an alternative treatment modality to conventional open surgical repair because of their low morbidity and mortality. 12,13 However, the hemodynamic stability of the patient, any associated comorbidities and concomitant injuries, and the suitability of the vascular anatomy for endovascular repair should all be assessed as part of patient selection. 14 Open surgery is still the best option for patients with unstable vital signs, and an endovascular approach can be applied to stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patient outcomes can be improved by prompt identification of iatrogenic damage and proper triage for additional treatment. For individuals with IVI, minimally invasive endovascular therapy may be an alternative [31].…”
Section: Management Preventionmentioning
confidence: 99%
“…Regardless of the controversy surrounding whether or not angiograms are necessary for penetrating injuries to the extremities, there are many more situations in which angiography is obviously required. Clearly, angiography is necessary before endovascular therapy [27,31]. Endovascular and minimally invasive procedures are increasingly used in the transitional stage of vascular surgery.…”
Section: Endovascular Treatmentmentioning
confidence: 99%
“…The complications of this method are those associated with any minimally invasive surgical procedure: vascular injury, damage to nearby organs, and infection [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The Society of Cardiovascular and Interventional Radiology and the American College of Radiology have shown that percutaneous nephrostomy is associated with less than 4% major bleeding or septic shock [ 17 ].…”
Section: Introductionmentioning
confidence: 99%